PREFERENSI BEBERAPA JENIS PATI DALAM PENGGUNAANNYA SEBAGAI EDIBLE COATING - . Mirnawati; . Seveline (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2019)
Melon is a type of fruit that has a high water content. High water content causes limited fruit storage, therefore it is necessary to preserve it to maintain the freshness of the melon. One method that can maintain the freshness of the fruit is edible coating. The purpose of this study was to determine the characteristics of organolepic melons given starch-based edible coatings from several types of tubers, namely cassava, canna, and lesser yam. This study used factorial Completely Randomized Design (CRD) with two factors. The first factor is the difference in CMC with a concentration of 1% and 1.5%. The second factor is the difference in glycerol with a concentration of 1% and 3%. The results of the study based on the ANOVA test showed that the type of starch treatment and the concentration between treatments did not have a significant effect on the texture, color, and aftertaste of the melon, but significantly affected the taste and aroma of the melon. So it can be concluded that from all edible coating formulations, panelists preferred the PS I formulation (cassava starch) with 1% CMC concentration and 1% glycerol.Keywords: cassava, canna, edible coating, lesser yam, melons